2019
DOI: 10.1021/acsabm.9b00445
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Regulation of Scaffold Stiffness for the Optimized Control of Cell Behavior

Abstract: The rigidity of extracellular matrices can impact cell fate, guide tissue development, and initiate tumor formation. Scaffolds such as hydrogels with tunable levels of stiffness have been developed to control cell adhesion, migration, and differentiation, providing suitable microenvironments for different tissue outcomes. However, studies of cell−material interactions are largely confined to biomaterials with stiffness values that are coarsely regulated, so refinements in sensitive cellular responses and optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 61 publications
(203 reference statements)
2
32
0
Order By: Relevance
“…The SFN layers slowed the release of DFO and there was significantly improved cell proliferation in the DFO-laden scaffolds with the slower DFO release rate. Besides better cytocompatibility, the aligned SFN layers induced the directional migration of HUVECs, which would also facilitate the cell infiltration and tissue ingrowth [ 28 , 36 ]. At day 3, significant migration was found for the cells cultured on the scaffolds with the aligned layers, while little migration occurred for cells cultured on the SF/HA-R and SF/HA-DFO-R scaffolds ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SFN layers slowed the release of DFO and there was significantly improved cell proliferation in the DFO-laden scaffolds with the slower DFO release rate. Besides better cytocompatibility, the aligned SFN layers induced the directional migration of HUVECs, which would also facilitate the cell infiltration and tissue ingrowth [ 28 , 36 ]. At day 3, significant migration was found for the cells cultured on the scaffolds with the aligned layers, while little migration occurred for cells cultured on the SF/HA-R and SF/HA-DFO-R scaffolds ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess cell migration behavior, HUVECs (2 ​× ​10 6 /scaffold) were seeded at the scaffold centers [ 36 ]. At specified times, all scaffolds were fixed and stained for observation using CLSM.…”
Section: Methodsmentioning
confidence: 99%
“…A plausible explanation for this behavior may be the imbalance between cell traction forces and corresponding ECM response, a crucial parameter for assembly of cell-matrix complexes and cell spreading. For instance, a study reported that the fine tuning of silk scaffold’s stiffness induces different endothelial migration and aggregation ( Lu et al, 2019 ), suggesting a sensitive dependence of cell migration on mechanical cues.…”
Section: Tailoring Silk Biomaterials To Control Cellular Fatementioning
confidence: 99%
“…Recently, beta-sheet rich SF nanofibers (BSNF) were assembled in aqueous solutions in our group, exhibiting superior biocompatibility and loading drug capacity to previous SF materials (Lu et al, 2011;Wu et al, 2016). BSNF as reinforcing nanofibers could be introduced to different hydrogels and scaffolds to tune the mechanical cues finely, resulting in controllable differentiation behaviors of stem cells Lu et al, 2019). Different cargos such as small molecules, growth factors, graphene sheets and gold nanoparticles were loaded on the nanofibers, which provided tunable physical and biochemical cues for cells and tissues (Ding et al, 2016b;Wu et al, 2016;Zhang et al, 2018;Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%